Wordpress-lisäosan kehitysprosessi - Hovila, Linda (2025)
Wordpress was originally designed to be a blogging platform, but it was later expanded to be content management system that can be used as a base of wide range of websites. Best way to add new features and expand Wordpress core is through plugins and Wordpress has made plugin development simple. However, the developing process is determined by the requirements of the plugin and it's funtionalities and they can change the process to be challenging. In this thesis, a plugin is developed from an existing tool and plugin development is examined through implementation.